New Small-Molecule Inhibitors Effectively Blocking Picornavirus Replication - Ford Siltz, Lauren A. (American Society for Microbiology, 2014)
Few drugs targeting picornaviruses are available, making the discovery of antivirals a high priority. Here, we identified and characterized three compounds from a library of kinase inhibitors that block replication of poliovirus, coxsackievirus B3, and encephalomyocarditis virus. Using an in vitro translation-replication system, we showed that these drugs inhibit different stages of the poliovirus life cycle. A4(1) inhibited both the formation and functioning of the replication complexes, while E5(1) and E7(2) were most effective during the formation but not the functioning step. Neither of the compounds significantly inhibited VPg uridylylation. Poliovirus resistant to E7(2) had a G5318A mutation in the 3A protein. This mutation was previously found to confer resistance to enviroxime-like compounds, which target a phosphatidylinositol 4-kinase IIIβ (PI4KIIIβ)-dependent step in viral replication. Analysis of host protein recruitment showed that E7(2) reduced the amount of GBF1 on the replication complexes; however, the level of PI4KIIIβ remained intact. E7(2) as well as another enviroxime-like compound, GW5074, interfered with viral polyprotein processing affecting both 3C- and 2A-dependent cleavages, and the resistant G5318A mutation partially rescued this defect. Moreover, E7(2) induced abnormal recruitment to membranes of the viral proteins; thus, enviroxime-like compounds likely severely compromise the interaction of the viral polyprotein with membranes. A4(1) demonstrated partial protection from paralysis in a murine model of poliomyelitis. Multiple attempts to isolate resistant mutants in the presence of A4(1) or E5(1) were unsuccessful, showing that effective broad-spectrum antivirals could be developed on the basis of these compounds. IMPORTANCE Diverse picornaviruses can trigger multiple human maladies, yet currently, only hepatitis A virus and poliovirus can be controlled with vaccination. The development of antipicornavirus therapeutics is also facing significant difficulties because these viruses readily generate resistance to compounds targeting either viral or cellular factors. Here, we describe three novel compounds that effectively block replication of distantly related picornaviruses with minimal toxicity to cells. The compounds prevent viral RNA replication after the synthesis of the uridylylated VPg primer. Importantly, two of the inhibitors are strongly refractory to the emergence of resistant mutants, making them promising candidates for further broad-spectrum therapeutic development. Evaluation of one of the compounds in an in vivo model of poliomyelitis demonstrated partial protection from the onset of paralysis.